Patient Safety Culture among Health Care Professionals in Saudi Arabia Hospital: Review of the Literature - Fayez J Alhrbi, Mohammed; Kim Lam, Soh (International Journal of Psychosocial Rehabilitation, 2020)
Many advanced countries, like the United States of America, the United Kingdom, and Australia, have dedicated the past few decades to the safety of lives by increasing the quality of research in the health sector, especially in patient safety culture, as a means towards achieving an improved health sector. Many people believe that Saudi Arabia’s health care system is among the best and safest medical care systems in the world, but little research has been dedicated to unraveling the practice of a safety culture existing within the care of health professionals in the hospitals of Saudi Arabia. As such, this research reviews the culture of safety literature within Saudi Arabia’s hospital setting.